Schistosoma Reflexus in Non-Descriptive Doe: A Rare Case Report - Shanmuganathan, Subramaniyan; Manikandan, Rajendran; Praveen, Vasudevan (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Schistosoma reflexus is commonly observed in ruminants, characterized by spinal inversion, evisceration of abdominal viscera, lung hypoplasia, positioning of the limbs adjacent to the skull, and an abnormal shape of the liver and rumen when distended with fluid. It has been observed most commonly in cattle (Roberts, 1998), buffaloes, occasionally in horses, rarely in goats (Hashemnia et al., 2013; Kumar et al., 2016), sheep, camels, and swine (Irwin and Pulley, 1996). This type of congenital anomaly occurs during the embryonic stage of the fetus. The etiology of congenital anomalies is unknown, but it may be due to genetic factors such as mutations, chromosomal anomalies, infectious agents, and environmental factors (Noakes et al., 2009). In this case study, dystocia due to a dead male Schistosoma reflexus fetal monster was relieved successfully by manual traction.